Del orgullo gay a la Diversidad Sexual: organización de identidades sexuales disidentes en El Salvador - Arévalo, Amaral Palevi Gómez (Diálogos Latinoamericanos, 2016)
This paper aims to analyze the process of organization of gay, lesbian, bisexual transvestite, transsexual, transgender and intersex identities (LGBTI) in San Salvador between 1992 and 2015. We identified four moments of this process: 1) The “Gay Pride” represents the initial moment of organization in the post-war period; 2) The “LGBTI” as result of the consolidation of identities; 3) The emergence of “Sexual Diversity” as a political player; and 4) “Making a difference without being different” that represents restricted social recognition. We used the concepts of sexual politics and symbolic actions for the analysis of each proposed historic moment. In conclusion, the LGBTI movement has promoted social questioning the binary patterns of sexuality as well as the gender essentialism, through symbolic actions. The sexual politics has focused on promoting the human rights of the LGBT population.